Disclosure Practices of Mobile Telecommunication Companies with Special Reference to Grameenphone Ltd. - Neogy , Taposh Kumar (Global Disclosure of Economics and Business, 2013)
This discussion highlights on the measurement and analysis of the nature of disclosure of the Grameenphone Ltd. during the period under study. The annual reports of the Grameenphone Ltd. were analyzed to determine the extent to which contained the items of information included in the disclosure index of the Grameenphone Ltd. during the period under study. An index of disclosure has been constructed to measure the extent of disclosure of Grameenphone Ltd. For analyzing the nature of disclosure of Grameenphone Ltd. researcher have analyzed the different part of disclosure index such as company profile items, accounting policy items, balances sheet assets items, balance sheet liabilities items and income statement items both debit and credit items. This study shows that the disclosure score of the Grameenphone Ltd. is satisfactory and there was significant and not significant difference in disclosure score between the difference years during the period under study of various items of disclosure index. GEL Classification Code: M41; M48